Contribution of Marine Phytoplankton and Bacteria to Alkalinity: An Uncharacterized Component. Issue 19 (1st October 2021) - Lee, Chang‐Ho; Lee, Kitack; Ko, Young Ho; Lee, Joon‐Soo
Abstract: The contributions of phytoplankton and bacteria cells to alkalinity (AT ) were measured in seawater samples obtained from 205 locations including the East Sea, the North Pacific Ocean, the Bering Sea, the Chukchi Sea, and the Arctic Ocean. We attributed the differences in AT values measured for unfiltered versus filtered samples to AT components contributed by phytoplankton (retained on a 0.7 μm filter) and by phytoplankton and bacteria combined (AT−BIO ; retained on a 0.45 μm filter). The AT−BIO values reached 10–19 μmol kg −1 in the East Sea and the North Pacific Ocean, and progressively decreased to a level of 1 μmol kg −1 with distance toward the Arctic Ocean. The study shows that the AT−BIO values are non‐negligible in coastal and open ocean environments and need to be considered when assessing the accuracy of carbon parameters calculated using the thermodynamic models that use measured AT as an input parameter. Plain Language Summary: In seawater thermodynamic calculations involving measured alkalinity, estimates of alkalinity contributed by bicarbonate and carbonate ions only are needed, and are made by correcting measured alkalinity values for contributions from borate and hydroxide ions, and from other minor chemical species. Among those minor components, contributions from phytoplankton and bacteria cells are an uncharacterized component of measured alkalinity. The present study shows that the contribution of particulate organic matter (mostly phytoplankton and bacteria) to measured alkalinity is significant in ocean environments. The common practice of making alkalinity measurements using unfiltered seawater in field studies could lead to overestimation of carbonate alkalinity when converting total alkalinity to carbonate alkalinity, because most total alkalinity data have been assumed to have negligible biological components. This overestimation could subsequently lead to errors in the calculated parameters. Thus the biological component in the total alkalinity needs to be taken into account when predicting carbon parameters using the thermodynamic models that use measured alkalinity as an input parameter. Key Points: Phytoplankton and bacteria cells contributed to alkalinity during the titration of seawater The biological components in alkalinity were non‐negligible in coastal and open ocean environments The biological components in alkalinity varied markedly depending on phytoplankton species in seawater